Combination of molecular alterations and smoking intensity predicts bladder cancer outcome1. Issue 4 (14th January 2013) - Mitra, Anirban P.; Castelao, Jose E.; Hawes, Debra; Tsao‐Wei, Denice D.; Jiang, Xuejuan; Shi, Shan‐Rong; Datar, Ram H.; Skinner, Eila C.; Stein, John P.; Groshen, Susan; Yu, Mimi C.; Ross, Ronald K.; et al.
Abstract BACKGROUND: Traditional single‐marker and multimarker molecular profiling approaches in bladder cancer do not account for major risk factors and their influence on clinical outcome. This study examined the prognostic value of molecular alterations across all disease stages after accounting for clinicopathological factors and smoking, the most common risk factor for bladder cancer in the developed world, in a population‐based cohort. METHODS: Primary bladder tumors from 212 cancer registry patients (median follow‐up, 13.2 years) were immunohistochemically profiled for Bax, caspase‐3, apoptotic protease‐activating factor 1 (Apaf‐1), Bcl‐2, p53, p21, cyclooxygenase‐2, vascular endothelial growth factor, and E‐cadherin alterations. "Smoking intensity" quantified the impact of duration and daily frequency of smoking. RESULTS: Age, pathological stage, surgical modality, and adjuvant therapy administration were significantly associated with survival. Increasing smoking intensity was independently associated with worse outcome (P < .001). Apaf‐1, E‐cadherin, and p53 were prognostic for outcome (P = .005, .014, and .032, respectively); E‐cadherin remained prognostic following multivariable analysis (P = .040). Combined alterations in all 9 biomarkers were prognostic by univariable (P < .001) and multivariable (P = .006) analysis. A multivariable model that included all 9 biomarkers and smoking intensity had greater accuracy in predicting prognosis than models composed of standard clinicopathological covariates without or with smoking intensity (P < .001 and P = .018, respectively). CONCLUSIONS: Apaf‐1, E‐cadherin, and p53 alterations individually predicted survival in bladder cancer patients. Increasing number of biomarker alterations was significantly associated with worsening survival, although markers comprising the panel were not necessarily prognostic individually. Predictive value of the 9‐biomarker panel with smoking intensity was significantly higher than that of routine clinicopathological parameters alone. Cancer 2013. © 2013 American Cancer Society.